EMPLOYEE S PERFORMANCE THORUGH EDUCATION AND TRAINING AS WELL AS RENUMERATION (A Case Study at SMK-SMTI Bandar Lampung) - Irawan, Aditya (Prosiding International conference on Information Technology and Business (ICITB), 2015)
Civil Servants as human resources have a very importantrole because the performance of the employee as a humanresource would affect the agencys success in achieving itsobjectives. Realizing that the man is a very importantdeterminant and the center of attention on everyoperational activity, each institution is required to managethe human resources that exist for the purpose that can beachieved by always being oriented to the use of humanresources more effectively and efficiently.This research is descriptive quantitative because themethod used in this study is a survey method usingquestionnaire technique. This research will be carried outat SMK-SMTI Bandar Lampung which is a verticalinstitution under Industrial Education and TrainingCenter, the Ministry of Industry of the Republic ofIndonesia by using a population of 70 respondents. Thereare three variables in this study; they are: 2 (two)independent variables Education and Training (X1) andPerformance Benefits (X2)) and 1 (one) dependentvariable. By the data processing it is found the hypothesiscan be answered that there is an influence of Educationand Training (X1) on Employee s Performance (Y), withthe total influence (R-square) as 48,4 %, it shows that theEducation and Training gives an effect as 48,4% on theEmployee s Performance. There is an influence ofPerformance Benefits (X2) on Employee s Performance(Y), with the total influence as 41,6 %, and it shows thatthe Performance Benefits gives an effect as 41,6% on theEmployee s Performance. There is an influence ofEducation and Training (X1), Performance Benefits (X2)on Employee s Performance (Y), with the total influenceas 56,1 %, it shows that the Education and Training andEmployee s Performance gives an effect as 56,1% on theEmployee s Performance.KEY WORDS: Education and Training, EmployeesBenefits, Employee s Performance